Bioprospecção de leveduras isoladas de kefir para aplicação em sorvetes probióticos - Cassanego, Daniela Buzatti (2018)
Kefir is considered a probiotic food, being different as it presents in its composition bacteria, yeasts and some fungi. From the literature review, it was concluded that there is a great variety when it comes to the yeasts that are part of the symbiotic complex of kefir grains, and such diversity depends on the type of substrate in which the grains are grown, as well as location, temperature and other factors. In relation to probiotic yeasts, there are many studies on possible strains with such potential; however, Saccharomyces boulardii is the largest representative of them. Possibly, different yeasts present in kefir may present a similar or better probiotic potential than Saccharomyces boulardii. The use of probiotic yeasts in food is restricted, however, ice-cream is presented as a good probiotic food carrier, since it does not undergo the fermentation process and yeasts can be added to the food in the lyophilized form. Thus, the aim was to isolate the yeasts from the kefir samples from the city of Santa Maria/RS, and identify them genetically through PCR for the purpose of, later, evaluate the probiotic potential of the identified yeast strains by in vitro technique. Nineteen yeast strains were isolated from six different kefir samples; but only three species from these microorganisms were identified: Saccharomyces cerevisiae, Hanseniospora uvarum and Kazachstania unispora. By simulating the passage of isolated strains through the gastrointestinal environment, it was observed that they could not be considered probiotics, once they did not show resistance to pancreatic digestion, according to the proposed methodology. With such results, the initial objective of managing one or more yeast strains isolated from kefir that presented probiotic potential in the ice-cream as food matrix was not possible. However, a probiotic ice-cream was elaborated using Saccharomyces boulardii yeast as a microorganism. This yeast has been already used since the 1950s as a probiotic, but in the lyophilized form as a medicine. In this context, two formulations of ice-cream were elaborated and evaluated, the control ice-cream and probiotic ice-cream. Survival tests of Saccharomyces boulardii yeast were performed up to 120 days of product storage. The results indicated that the ice-cream samples (control ice-crem and probiotic ice-cream) are in accordance with parameters recommended by the Brazilian legislation and are similar to results found in the literature. In relation to the survival tests of Saccharomyces boulardii, it was observed that it presented viability for up to 90 days of ice-cream storage, at temperature -18 oC. The results showed that even though yeasts isolated and identified in regional kefir do not present probiotic potential, the use of the probiotic yeast Saccharomyces boulardii presented satisfactory results when evaluating its survival in probiotic ice-cream. Nevertheless, further studies on the subject must be carried out for the commercialization of this innovative probiotic ice-cream.